Cybersecurity education for awareness and compliance - Vasileiou, Ismini 1980; Furnell, Steven 1970 (Advance in Information Serurity,Privacy, and Ethics (AISPE) Book Series, 2019)
"This book provides businesses and organizations with a clear understanding of what security education is, the elements required to achieve it, and how to instill good security behavior and compliance. The chapters draw upon both theoretical principles and practical experience in order to consider what must be done and how to achieve it"--